High-throughput analysis using 16S rRNA sequencing of bacterial communities associated in selected mangrove species from Bayug Island, Iligan City, Philippines - STEFENIE KATRIN V. SIBLOS; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Siblos SKV, Tabugo SR. 2023. High-throughput analysis using 16S rRNA sequencing of bacterial communities associated in selected mangrove species from Bayug Island, Iligan City, Philippines. Biodiversitas 25: 53-61. Mangrove ecosystems are recognized globally as highly productive ecosystems, that play a crucial role in carbon sequestration, erosion control, water purification, and as essential breeding grounds for diverse aquatic life. They also offer specialized ecological niches, accommodating a diverse range of organisms, including bacterial communities. This study aimed to investigate bacterial communities of Bayug Island in Iligan City, Philippines, inhabiting six mangrove species, namely Rhizophora stylosa Griffith, Rhizophora apiculata Blume, Rhizophora mucronata Lam., Sonneratia alba Sm., Ceriops tagal (Perr.) C.B.Rob., and Nypa fruticans Wurmb and their possible functions within the mangrove forests. Genomic DNA was extracted from the six pooled soil samples, and the V3-V4 region of the 16S rRNA gene was sequenced using the Illumina MiSeq platform. Six amplicon libraries, corresponding to the mangrove species were analyzed with Parallel Meta Suite software, yielding 173,270 amplicon sequence variants (ASVs) after quality control. The study identified the top five most abundant ASVs in the mangrove rhizosphere, linked to the genera Vibrio, Stenotrophomonas, Serratia, Pseudoalteromonas, and Achromobacter. Among the mangrove species, S. alba exhibited higher alpha diversity according to the Shannon index. PICRUSt analysis revealed that microorganisms are involved in biodegradation, xenobiotic metabolism, and other metabolic processes within the mangroves. These bacteria could find applications in environmental cleanup, bioremediation, waste treatment, and soil health improvement. This result contributes to the ongoing ecological restoration of mangrove forests at the research site.